Deciphering the role of exogenously-applied vanillic acid in regulating drought stress tolerance in pea (Pisum sativum L.): Key growth and physio-biochemical attributes - Abdul Rahman; Nudrat Aisha Akram; Muhammad Ashraf; Abdulaziz Abdullah Alsahli; Parvaiz Ahmad (Journal of King Saud University: Science)
To investigate the impact of exogenously applied vanillic acid (VA) in mitigating the adverse effects of drought stress, a greenhouse experiment was conducted on pea plants (Pisum sativum L.). The pea seeds were primed for 14 h in varying concentrations (0, 0.5, 1.0, 2.0, 3.0, 4.0, 5.0, and 6.0 mM) of VA Then, thirty-five days old pea plants were subjected to control (100 % field capacity) and water deficit conditions (60 % F.C.). After thirty days of water stress treatments, the data showed a notable reduction in shoot and root fresh and dry weights, shoot and root lengths, and chlorophyll contents. While, water deficit stress led to an increase in leaf free proline, total phenolics, glycinebetaine (GB), ascorbic acid AsA) as well as the activities of catalase (CAT), superoxide dismutase (SOD) and peroxidase (POD) enzymes. We observed that seed priming with various concentrations of vanillic acid resulted in significant enhancement in shoot and root fresh and dry weights, shoot and root lengths, chlorophyll contents, proline, total phenolics, GB, AsA and the activities of POD, SOD and CAT enzymes of pea plants. Of varying concentrations of VA, 2.0 and 4.0 mM VA were more effective in improving the plant morphology and physio-biochemical metabolites of pea plants. So the results of the present study suggested that the improvement in growth and different physio-biochemical characteristics can be attributed to the VA-induced upregulation of osmoprotection and oxidative defense system of pea plants.